Building Together : Succesful Partnerships Between Community and the Health and Social Services System - Community Health and Social Services Network (CHSSN) (2017)
The Community Health and Social Services Network (CHSSN) coordinates a Quebec-wide health and social services “Adaptation Program” designed to enhance the vitality of English-speaking minority communities in Quebec by increasing access to existing health and social services for Englishspeaking Quebecers. The program is supported by an investment from Health Canada and has been undertaken in partnership with the ministère de la Santé et des Services sociaux (MSSS). An implementation agreement between CHSSN and the MSSS was concluded to incorporate the projects into Quebec’s initiatives to improve access to health and social services in English through partnerships between local English-speaking communities and health and social services system.
Keywords: Official Language Minority Community (OLMC)

Portrait of the English-speaking Community of Rouyn-Noranda - Richardson, Mary (Community Health and Social Services Network (CHSSN), 2015)
This portrait has been completed by Neighbours and the Community Health and Social Services Network (CHSSN), in collaboration with the Centre intégré de santé et des services sociaux (CISSS), the city of Rouyn-Noranda (Villes et villages en santé) and the local English school, Noranda School. Neighbours is a non-profit community organization established to serve the Englishspeaking population of the Rouyn-Noranda area through facilitating information sharing, defending the right of access to service in English and organizing social and cultural events. Neighbours is committed to strengthening networks within the English and French speaking population as well as encouraging community development initiatives. The main objective of this portrait is to contribute to a more in-depth understanding of the English-speaking community of Rouyn-Noranda in order to address the issues it faces.
Keywords: Official Language Minority Community (OLMC)

English Health Partnership Annual Report 2011-2012 - Neighbours Regional Association of Rouyn-Noranda (2012)

Baseline Data Report 2009-2010 : Demographic Profiles of Quebec's English-speaking Communities by selected CSSS Territories - Pocock, Joanne; Warnke, Jan (Community Health and Social Services Network (CHSSN), 2010)
This document presents selected demographic characteristics of the English-speaking population of the CSSS territories in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI) of the Community Health and Social Services Network (CHSSN). The information presented is drawn from the 2006 Census of Canada. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec's official language minoritty community.
Keywords: Official Language Minority Community (OLMC)

Summary of the English-language Health and Social Services Access Program for the English-speaking Population of Rouyn-Noranda - Neighbours Regional Association of Rouyn-Noranda